2014
DOI: 10.1007/s11581-014-1322-x
|View full text |Cite
|
Sign up to set email alerts
|

A technical review on gas diffusion, mechanism and medium of PEM fuel cell

Abstract: The operation of polymer electrolyte membrane (PEM)-based fuel cells involves numerous physicochemical processes and components actively governing its function and, among them, gas transport phenomena and gas diffusion layer (GDL) are noteworthy, and the present paper provides a comprehensive assessment on gas diffusion mechanism, geometry of GDL components and related modelling studies involved in GDL fabrication. The impact of GDL on diffusion of reactants, water management and the transport of ions has also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(57 citation statements)
references
References 151 publications
(184 reference statements)
2
53
0
2
Order By: Relevance
“…It can be found that some AM technologies can be used to fabricate more than one component in a fuel cell . For example, selective laser sintering (SLS) from the group of powder bed fusion has been demonstrated to fabricate different functional components in a single PEMFC, i.e., the aluminide‐made gas diffusion layer (GDL) and the graphite‐made flow field plates , , . Besides, Table also shows that certain fuel cell components can be fabricated using more than one AM technology.…”
Section: Additive Manufacturing Technologies For Fuel Cell Applicationmentioning
confidence: 99%
“…It can be found that some AM technologies can be used to fabricate more than one component in a fuel cell . For example, selective laser sintering (SLS) from the group of powder bed fusion has been demonstrated to fabricate different functional components in a single PEMFC, i.e., the aluminide‐made gas diffusion layer (GDL) and the graphite‐made flow field plates , , . Besides, Table also shows that certain fuel cell components can be fabricated using more than one AM technology.…”
Section: Additive Manufacturing Technologies For Fuel Cell Applicationmentioning
confidence: 99%
“…GDL is usually made of two different layers, whose combination should impart these properties: one is a macro-porous layer, sometimes called back diffusion layer, and the second one is named micro-porous layer. Both are carbon-based, but to reach the desired hydrophobic properties a PTFE coating of the entire GDL is needed [4]. In this study the bases to create an entire "one piece" GDL are placed, in order to simplify the obtaining of the usual one.…”
Section: Gomentioning
confidence: 99%
“…Each electrode consist of at least a catalyst layer (CL) and a gas diffusion layer (GDL). GDL is an integral part of a PEMFC and its principal functions are to efficiently transport the reactants and the products to and from the CL as well as to conduct heat and current between CL and bipolar plates (BPs) , . In a PEMFC stack, several cells are stacked in series with compression.…”
Section: Introductionmentioning
confidence: 99%